Prosthodontic Rehabilitatative Therapy through Surgical Obturator for Maxillectomy Patients: A Review - Rathee, Manu; Bhoria, Mohaneesh; Malik, Poonam (Cancers Review, 2014)
The maxillofacial patient experiences a unique alteration in the normal oral/craniofacial environment and functions, which are the results of congenital, traumatic or surgical insults. Maxillofacial Prosthetics aimed to attain the optimal functions, such as speech and swallowing, and normalcy of surrounding structure. The provision of surgical obturator is one step in achieving normalcy, as it allows covering the deficiencies/defects to regain optimal/suboptimal functions immediately after surgical resection. This paper provides an overview on the designing principles, goals and role of surgical obturator in rehabilitating maxillectomy cases.